2016
DOI: 10.1007/s11427-016-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac BIN1 (cBIN1) is a regulator of cardiac contractile function and an emerging biomarker of heart muscle health

Abstract: In recent decades, a cardiomyocyte membrane scaffolding protein bridging integrator 1 (BIN1) has emerged as a critical multifunctional regulator of transverse-tubule (t-tubule) function and calcium signaling in cardiomyocytes. Encoded by a single gene with 20 exons that are alternatively spliced, more than ten BIN1 protein isoforms are expressed with tissue and disease specificity. The recently discovered cardiac alternatively spliced isoform BIN1 (cBIN1 or BIN1+13+17)plays a crucial role in organizing membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
9
1
2
Order By: Relevance
“…On the other hand, the factors underlying E-C coupling efficiency include sarcoplasmic reticulum (SR). RyRs sensitivity [16], SERCA function [17,18] as well as T-tubule structure [19]. In the present study, miR-331-3p was not predicted to bind either RyR2 or SERCA mRNA.…”
Section: Discussioncontrasting
confidence: 50%
“…On the other hand, the factors underlying E-C coupling efficiency include sarcoplasmic reticulum (SR). RyRs sensitivity [16], SERCA function [17,18] as well as T-tubule structure [19]. In the present study, miR-331-3p was not predicted to bind either RyR2 or SERCA mRNA.…”
Section: Discussioncontrasting
confidence: 50%
“…They have been observed in skeletal muscles of endurance athletes and their activation entrains complex pathways that enhance physical 73 and racing performance 74 . Isoforms of BIN1 , are important in the formation of transverse tubules which play a role in skeletal and cardiac muscle contractility and relation 75 , 76 . The selection of MSTN , BIN1 and HIF-1 associated genes could have arisen as an adaptive response to endure physical exhaustion arising from long-term long distance walking.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we found that cBIN1-microdomain is also critical in organizing the intracellular distribution of SERCA2a for diastolic calcium regulation ( Liu et al, 2020 ). In HF, cBIN1-microdomains are disrupted due to transcriptional reduction in cBIN1 ( Hong et al, 2012b ; Caldwell et al, 2014 ; Zhou and Hong, 2017 ), impairing dyad formation, calcium transient regulation, and cardiac contractility. Reduced myocardial cBIN1 can be detected in human blood, a result of cBIN1-membrane turnover and microparticle release ( Xu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%